JOB SATISFACTION AMONG MALE NURSES WORKING AT PUBLIC AND PRIVATE HOSPITALS - Mairaj Hafeez; Parveen Akhtar; Abdul Wahab Channa; Asadullah Rind; Aftab Ahmed Chandio; Ms. Nasreen Channa (International Journal of Contemporary Issues in Social Sciences, 2024)
Background: Job satisfaction is a topic of wide interest to people who work in both public and private organizations. It is a most frequently studied variable in organizational researches and also a central variable in both research and theory. Shortage of male nurses has been a constant challenge for the nursing profession in Pakistan and job satisfaction is a major cause of this shortage among health care providers. Objectives: To compare the level of Job Satisfaction among male nurses of public and private hospitals. Methodology: A descriptive cross sectional study was conducted at Isra university hospital and Liaquat university hospital. A sample size of 132 male nurses was drawn from the population of 200 male nurses and convenient sampling technique was used for the data collection. A well defined questioner related to job satisfaction was used as a data collection instrument. Results: The results showed that mean age of the respondents was 32 years and standard deviation + was7.7. Job satisfaction between public and private hospitals showed that male nurses 91(69%) of public hospital were more satisfied than male nurses 25(19%) of private hospital, p value <0.05 showed a highly significant and strong correlation between factors (pay, promotion, supervision, fringe benefits, operating conditions and nature of work) and job satisfaction. Conclusion: Present study showed that the common influential factors which were satisfying the male nurses of public hospital were pay, fringe benefits, promotion and nature of work. In private hospital the influential factor was supervision.